Infeksi COVID-19 pada kehamilan dengan insulin dependent diabetes mellitus (IDDM) - Arif Rahman Nurdianto; Rizal Fauzi Nurdianto; Dyah Ayu Febiyanti (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Research on pregnancies with insulin dependent diabetes mellitus (IDDM) infected with COVID-19 is very limited. In pregnant conditions, there is a shift from Th1 to Th2 and physiological changes that make it very susceptible to being infected by COVID-19 in pregnancy, in addition to complaints that are similar between changes due to pregnancy and symptoms of COVID-19. The aim of this study was to Explain the effect of COVID-19 infection in pregnant women with IDDM. This study was conducted using a descriptive method of clinical and laboratory examination results of one pregnant patient aged 26 years with IDDM and infected with COVID-19 at the Trosobo Health Center. The variables in this study were the results of clinical and laboratory examinations of patients during treatment. All data were then analyzed descriptively according to the latest journal literature. Result of this study showed that Pregnant women with IDDM and infected with COVID-19 might have disorders of the lung organs in the form of pneumonia on X-rays, disturbances in laboratory test and minor clinical disorders. In addition, it is important to note that the presence of heart problems as indicated by disturbances in the rhythm of the post partum ECG. COVID-19 infection in pregnant women with IDDM can show mild or severe symptoms such as heart problems and further research is needed on the effect of this infection with a larger sample.